The role of the midwife in puerperium care of women with HELLP syndrome, considering the impact of the disease on the mother-child relationship - Budna, Paulina; Szablewska, Anna W. (Nursing Problems / Problemy Pielęgniarstwa, 2023)
HELLP syndrome is a disease whose symptoms include haemolysis, elevated liver enzymes, and significantly reduced platelet counts. Usually, this pathology is a severe complication of pre-eclampsia, and it reveals itself between the 27th and 37th weeks of pregnancy or during the first 48 hours of postpartum puerperium. It is a relatively rare condition, diagnosed in fewer than 1% of pregnant women. Clinical manifestations are nonspecific, variable, and mainly dependent on the circulatory system. In many cases, this pregnancy complication results in the mother and child being separated, causing the disruption of lactation initiation and rela-tionship building. Consequently, the newborn may have difficulty adapting to ectopic conditions. The aim of our ‘case study’ is to present characteristics of HELLP syndrome and the difficulties posed for relationship building. The nursing process was developed using the ICNP® method.